The Implications of Foreign Investment Limitations on 'The End Justifies the Means' Practices within the Indonesian Investment Sector - Akbar, M. Aidil; Ritonga, Wildan Ambron; Putra, Rifqi Pratama (Civiliza Publishing, 2025)
This study aims to analyze the implications of Presidential Regulation (Perpres) Number 49 of 2021 on the emergence of